Potential roles of stigma exsertion on spikelet fertility in rice (Oryza sativa L.) under heat stress - Qi, Beibei; Wu, Chao (Frontiers in Plant Science, 2022)
Heat stress during the flowering stage induces declining spikelet fertility in rice plants, which is primarily attributed to poor pollination manifesting as insufficient pollen deposited on the stigma. Plant pollination is associated with anther dehiscence, pollen dispersal characteristics, and stigma morphology. The mechanisms underlying the responses of spikelet fertility to heat stress have been clarified in depth in terms of the morphological and behavioral characteristics of the male reproductive organs in rice. However, the roles of female reproductive organs, especially the stigma, on spikelet fertility under heat conditions are unclear. The present study reviews the superiority of stigma exsertion on pollen receptivity under heat during the flowering stage and discusses the variations in the effects of exserted stigma on alleviating injury under asymmetric heat (high daytime and high nighttime temperatures). The pollination advantages of exserted stigmas seem to be realized more under high nighttime temperatures than under high daytime temperatures. It is speculated that high stigma exsertion is beneficial to spikelet fertility under high nighttime temperatures but detrimental under high daytime temperatures. To cope with global warming, more attention should be given to rice stigma exsertion, which can be manipulated through QTL pyramiding and exogenous hormone application and has application potential to develop heat-tolerant rice varieties or innovate rice heat-resistant cultivation techniques, especially under high nighttime temperatures.